Level of compliance to organic agricultural practice in the practical year training programme of University of Ibadan, Nigeria (2015)
The study assessed compliance to organic agricultural practice in the practical year training programme (PYTP) of the University of Ibadan, Nigeria. .A total of 122 PYTP students were sampled. Data were collected through well-structured questionnaire and analysed with frequency counts, percentages and means. Study revealed that 73.1% have high level of knowledge on organic agriculture. Quest to meet up with required planted crops 'amaranths, celosia and chocorust yield, weed control and pest and diseases were the top constraints to compliance. Less than half (47.8%) of respondents had a high level of compliance. However high knowledge of organic agricultural practices did not translate to high level of compliance to standard practice. Students must be made to adhere strictly to principles being taught by the instructor and other means of grading rather than yield should be employed.